Beelouse, Braula coeca Nitzsch (Insecta: Diptera: Braulidae) - Howard V. Weems, Jr.; Malcolm T. Sanford (EDIS)
The beelouse, Braula coeca Nitzsch 1818, is a tiny commensalate wingless fly found in colonies of the honey bee, Apis mellifera Linnaeus, where it lives on the bodies of the bees and literally steals its food out of the mouth of its host. The beelouse is in the family Braulidae, comprising two genera, Braula and Megabraula, contains eight species (see Papp 1984f; Huttinger 1980; Grimaldi and Underwood 1986). This document is EENY-171 (originally published as DPI Entomology Circular 252), one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2000.